The Philippines Sustainable Livelihood Program : Providing and Expanding Access to Employment and Livelihood Opportunities - Acosta, Pablo A. (World Bank, Washington, DC, 2018)
The Philippines Department of Social Welfare and Development has taken the lead in providingopportunities for income generating activities/livelihood development through the implementationof the Sustainable Livelihood Program (SLP) since 2011, with the objective to reduce poverty andinequality by generating employment among poor households and by moving highly vulnerablehouseholds into sustainable livelihoods and toward economic stability. This note describes the design and core processes of the SLP and reflects on the opportunities that the program has to improve and complement other Social Protection programs to make an impact on households’ welfare, and provides recommendations to maximize its impact.